THE POTENCY OF LUBUK LARANGAN JORONG IKAN BANYAK AS LOCAL WISDOM BASED ECOTOURISM AREA - Fiona Novianti; Muhammad Fauzi; Adriman Adriman (Berkala Perikanan Terubuk, 2019)
This study  aims to understand the local wisdom and the feasibility of the area as an ecological tourism object has been carried out from February to March 2018. The method used in this study is the survey method. Water quality data collection was carried out four times (once/two weeks), while questionnaires were distributed prior to environmental data collection. Water samples were taken from three stations, while local wisdom data were collected through questionnaires. Results shown that the community used to maintain the Jorong Ikan Banyak ecosystem by applying regulations for fish capture. Water quality parameter values of the Lubuk Larangan are as follows : temperature was 22.5-230c; water depth was 71.75-120.25 cm; current speed  was 0.25-0.42 m/s; dissolved oxygen was 4.6-4.8 mg/l and pH was 6. The tourism potential element scores of the Lubuk Larangan were as follows:  Attractiveness 1,095; Accessibility 537.5; Accommodations 45 and Facilities 240, total score  1,917.5. This score indicates that the Lubuk Larangan Jorong Ikan Banyak  is suitable for tourism object.